Report Of The Chief-Inspector Of Mines In India,Under The Indian Mines Act (Viii Of 1901), For The Year Ending 31St December 1908 To 1913 - Willson, J.R.R.; Adams, G.F; Simpson, R.R. (Calcutta Supritendant of Government Printing, 1909)
Mines